Pituispheres Contain Genetic Variants Characteristic to Pituitary Adenoma Tumor Tissue - Peculis, Raitis; Mandrika, Ilona; Petrovska, Ramona; Dortane, Rasma; Megnis, Kaspars; Nazarovs, Jurijs; Balcere, Inga; Stukens, Janis; Konrade, Ilze; Pirags, Valdis; Klovins, Janis; Rovite, Vita (Frontiers in Endocrinology, 2020)
The most common type of pituitary neoplasms is benign pituitary adenoma (PA). Clinically significant PAs affect around 0.1% of the population. Currently, there is no established human PA cell culture available and when PA tumour cells are cultured they form two distinct types depending on culturing conditions either free-floating aggregates also known as pituispheres or cells adhering to the surface of cell plates and displaying mesenchymal stem-like properties. The aim of this study was to trace the origin of sphere-forming and adherent pituitary cell cultures and characterize the potential use of these surgery derived cell lines as PA model. We carried out a paired-end exome sequencing of patients’ tumour and germline DNA using Illumina NextSeq followed by characterization of corresponding PA cell cultures. Variation analysis revealed a low amount of somatic mutations (mean = 5.2, range 3 - 7) in exomes of PAs. Somatic mutations of the primary surgery material can be detected in the exomes of respective pituispheres, but not in exomes of respective mesenchymal stem-like cells. For the first time, we show that the genome of pituispheres represents genome of PA while mesenchymal stem cells derived from the PA tissue do not contain mutations characteristic to PA in their genome, therefore, most likely representing normal cells of pituitary or surrounding tissues. This finding indicates that pituispheres can be used as a human model of PA cells, but combination of cell culturing techniques and NGS needs to be employed to adjust for disability to propagate spheres in culturing conditions.